2019
DOI: 10.1101/782227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translational efficiency across healthy and tumor tissues is proliferation-related

Abstract: 11Background: Different tissues express genes with particular codon usage and anticodon 12 tRNA repertoires. However, the codon-anticodon co-adaptation in humans is not completely 13 understood, as well as its effect on tissue-specific protein levels. 14 Results:We first validated the accuracy of small RNA-seq for tRNA quantification across 15 five human cell lines. We then analyzed tRNA expression in more than 8000 tumor samples 16 from TCGA, together with their paired mRNA-seq and proteomics data, to determi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…S3, A and B). Similar to tRNA expression in other systems (43)(44)(45), however, some tRNA genes showed severely biased expression levels in zebrafish embryos. For example, 75 to 86% of total tRNAs at any examined developmental stages were tRNA His/GTG that has 511 gene copies in the genome (Fig.…”
Section: Results Trnafs Expressed In a Dynamic Level And Pattern During Zebrafish Early Embryogenesissupporting
confidence: 65%
“…S3, A and B). Similar to tRNA expression in other systems (43)(44)(45), however, some tRNA genes showed severely biased expression levels in zebrafish embryos. For example, 75 to 86% of total tRNAs at any examined developmental stages were tRNA His/GTG that has 511 gene copies in the genome (Fig.…”
Section: Results Trnafs Expressed In a Dynamic Level And Pattern During Zebrafish Early Embryogenesissupporting
confidence: 65%
“…Our analysis showed that the fine-tuned regulation of transcripts enriched in A/T-ending codons could be directly related to the specific regulation of tRNAs with anticodons recognizing A/T-ending codons. Therefore, we used the Supply-to-Demand Adaptation (SDA) codon values to obtain a global estimate of translation efficiency [22]. We compared the SDA values from healthy samples for codons enriched in the negative pole component against those in the positive pole (see Figure 2D).…”
Section: Trna Expression Profilesmentioning
confidence: 99%
“…The observed coordination could reflect a greater variation of the tRNA pool related to A/T-ending codons than that of G/C-ending codons. Harnessing recently published data on tRNA abundance [22], we explored the variation of tRNA across healthy tissues. We found that the coefficient of variation among tissues was higher for the pool of tRNAs with A or U in the position 34 of the anticodon than for tRNAs with G or C (Figure 6A, Supplementary Table 8).…”
Section: Trna Expression Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Brf1 overexpression in a mouse model of prostate cancer accelerates the disease, indicating that increases in tRNA expression may promote certain tumours, although it is possible that this phenotype is driven by upregulation of specific tRNAs (Loveridge et al, 2019). Importantly, the tRNAs induced in cancer cells favour a pro-proliferative programme and their upregulation is associated with a worse prognosis (Gingold et al, 2014;Hernandez-Alias et al, 2019).…”
Section: Control Of Trna-dependent Decoding and Its Role In Diseasementioning
confidence: 99%